Bodies of Sound / : Becoming a Feminist Ear - Revell, Irene; Shin, Sarah (S.l. : Silver Press, 2024)
Sara Ahmed, Ximena Alarcón, Svetlana Alexievich, Ain Bailey & Frances Morgan, Anna Barham, Xenia Benivolski, Leanne Betasamosake Simpson & Kite, Elena Biserna, Karen Barad & Black Quantum Futurism, Anne Bourne, Daniela Cascella, Theresa Hak Kyung Cha, Maria Chávez, Don Mee Choi, Carson Cole Arthur, Petero Kalulé & AM Kanngieser, Lindsay Cooper, Julia Eckhardt, Lucia Farinati & Claudia Firth, Ella Finer, Annie Goh, Louise Gray, Christina Hazboun, Johanna Hedva, Sarah Hennies, Tomoko Hojo, IONE, Lee Ingleton, Hannah Catherine Jones, Christine Sun Kim, Nat Lall, Cathy Lane, Jeanne Lee & Lona Foote, Marysia Lewandowska, Annea Lockwood & Jennifer Lucy Allan, Cannach MacBride, Elaine Mitchener & Hannah Kendall, Alison O'Daniel, Naomi Okabe, Pauline Oliveros, Daphne Oram, Gascia Ouzounian, Holly Pester, Roy Claire Potter, Anna Raimondo, Tara Rodgers, Aura Satz & Barbara London, Shortwave Collective, Sisters of the Order of Celestial Nephology, Sop, Syma Tariq, Marie Thompson, Trinh T. Minh-ha & Stoffel Debuysere, Salomé Voegelin
boek